A method for screening groundwater vulnerability from subsurface hydrocarbon extraction practices. (1st November 2019) - Loveless, S.E.; Lewis, M.A.; Bloomfield, J.P.; Davey, I.; Ward, R.S.; Hart, A.; Stuart, M.E.
Abstract: This paper describes a new screening method for assessing groundwater vulnerability to pollution from hydrocarbon exploitation in the subsurface. The method can be used for various hydrocarbon energy sources, including conventional oil and gas, shale gas and oil, coal bed methane and underground coal gasification. Intrinsic vulnerability of potential receptors is assessed at any particular location by identifying possible geological pathways for contaminant transport. This is followed by an assessment of specific vulnerability which takes into account the nature of the subsurface hydrocarbon activity and driving heads. A confidence rating is attached to each parameter in the assessment to provide an indication of the confidence in the screening. Risk categories and associated confidence ratings are designed to aid in environmental decision making, regulation and management, highlighting where additional information is required. The method is demonstrated for conventional gas and proposed shale gas operations in northern England but can be adapted for use in any geological or hydrogeological setting and for other subsurface activities. Highlights: Screening method to assess groundwater vulnerability to pollution from subsurface. Used for various hydrocarbon energy sources. Designed to aid in environmental decision making, regulation and management. Can be adapted for any hydrogeological setting and other subsurface activities.